Local labor impact of wind energy investment: An analysis of Portuguese municipalities - Costa, Hélia (2021)
Investment in wind power has grown remarkably in the past decades in Portugal. Although economic development is an argument for investment incentive policies, little evidence exists as to their net impact on local-level unemployment. Using data for all 278 Portuguese mainland municipalities for the years 1997-2017, we assess the existence, distribution and duration of local-level labor impacts of wind power investment. Our results show there are short-term effects during the construction phase. We estimate a decrease of 0.17 and 0.23 percentage points in the total unemployment rate per 100 MW of installed power in each of the two years of the construction phase. These effects are felt mainly for unskilled labor and male workers. Further analysis of spatial interaction finds positive spatial spillovers for municipalities that are 30 km or less away but not farther, implying workers are willing to commute but not migrate. We find a very small sustained impact during the operations and maintenance phase, despite both short- and long-term impacts on municipalities' revenues. (C) 2020 Elsevier B.V. All rights reserved.